PENGARUH SUBTITUSI EKSTRAK KEDELAI TERHADAP KARAKTERISTIK SELULOSA BAKTERI Acetobacter xylinum DALAM PEMBUATAN NATA DE SWEET POTATO - Nur Azizah Basalamah; Ilah Nurlaelah; Handayani Handayani (Quagga : Jurnal Pendidikan dan Biologi, 2018)
Sweet potato white ac varieties is a sweet potato endemic of Kuningan, but the conventional way of processing causes sweet potato is less desirable by consument. High carbohydrate content in sweet potato makes it potentially to be the main ingredient of making nata. Nata is a bacterial cellulose were made from glucose by Acetobacter xylinum bacteria. The manufacturing process of nata uses ZA as an additional source of nitrogen. However, the use of ZA raises concerns about its safety for food. The high content of protein in soy extract has the potential to replace ZA in making nata. The purpose of this study was to determine the effect of soybean extract as a source of nitrogen to the characteristics of nata de sweet potato. In this study there are seven treatments and two controls, namely F1 (68.6 ml). F2 (73.6 ml), F3 (78, 6 ml), F4 (83.6 ml), F5 (88.6 ml), F6 (93.6 ml), and F7 (98.6 ml). The data obtained were thickness of nata de sweet potato analyzed by anova test and BNT test and organoleptic data to know the level of consumer preference. The results showed that there was a significant effect on the nata de sweet potato characteristic shown by Fcount Ftable, that is 75 3,71 ith the significance level of 0.01. The use of soybean extract at F4 treatment (83.6 ml) is the thickest and most likely by the panelists. The use of soy extract of 83.6 ml can replace the use of ZA in making nata.Keyword : Soybean, Bacterial Cellulose, Nata de sweet potato